Solid acetone structure dependence on pressure: a new fibre textured thin film crystallographic structure studied by grazing-incidence X-ray diffraction. Issue 42 (11th October 2016) - Ferrer, P.; da Silva, I.; Puente-Orench, I.
Abstract : Acetone thin films were crystallized directly from its vapour phase under UHV conditions at 120 K on two different substrates and studied them using GI-XRD. Abstract : Recently, the development of miniaturized gas-sensing devices, particularly for toxic gas detection and pollution monitoring, has been the subject of intense research. A wide range of materials are available for acetone sensors, where the competition between the intermolecular forces and the molecule–substrate interactions plays a crucial role. Despite this, the structural behaviour of acetone with temperature is still not fully understood. In this work, by varying the chemical vapour deposition rate on two different substrates at 120 K, two distinct acetone crystal structures were observed using grazing incidence X-ray diffraction. Together with a randomly oriented polycrystalline structure of the known orthorhombic phase, a new well-ordered fibre textured thin film structure with a related monoclinic structure was obtained. The phase obtained appears to be only dependent on the vapour deposition pressure and not on the type of substrate, that is, the acetone crystal structure is controlled by the intermolecular forces, while substrate interactions do not seem to play any significant role. The significance of forming a fibre textured thin film structure in this manner is discussed.